Emotion processing and psychogenic non-epileptic seizures: A cross-sectional comparison of patients and healthy controls. (July 2015) - Novakova, Barbora; Howlett, Stephanie; Baker, Roger; Reuber, Markus
Highlights: PNES patients reported greater emotion processing deficits than healthy volunteers. Impaired emotion processing was associated with greater psychological distress. Deficits in emotion processing were related to more severe somatic symptoms. Impaired emotion processing was associated with threatening view of the symptoms. Emotion processing problems were associated with reduced mental health functioning. Abstract: Purpose: This exploratory study aimed to examine emotion-processing styles in patients with psychogenic non-epileptic seizures (PNES), compared to healthy individuals, and to explore associations of emotion processing with other psychological measures and seizure frequency, using the new Emotional Processing Scale (EPS-25), which had not previously been used in this patient group. Methods: Fifty consecutive patients with PNES referred for psychotherapy completed a set of self-report questionnaires, including the Emotional Processing Scale (EPS-25), Clinical Outcome in Routine Evaluation (CORE-10), Short Form-36 (SF-36), Patient Health Questionnaire (PHQ-15), and Brief Illness Perception Questionnaire (BIPQ). Responses on the EPS-25 were compared to data from 224 healthy controls. Results: Patients with PNES had greater emotion processing deficits across all dimensions of the EPS-25 than healthy individuals (suppression/unprocessed emotion/unregulated emotion/avoidance/impoverished emotional experience). Impaired emotion processing was highly correlated with psychological distress, more frequent and severe somatic symptoms, and a more threatening understanding of the symptoms. Emotion processing problems were also associated with reduced health-related quality of life on the mental health (but not the physical health) component of the SF-36. The unregulated emotions sub-scale of the EPS was associated with lower seizure frequency. Conclusion: The results showed clear impairments of emotion processing in patients with PNES compared to healthy individuals, which were associated with greater psychological distress and reduced mental health functioning. These findings seem to support the face validity of the EPS-25 as a measure for PNES patients and its potential as a tool to assess the effectiveness of psychological interventions.